Relationship between peak power and performance in well-trained throwers - Bouhlel, E.; Chelly, S.; Gmada, N.; Rebai, H.; Tabka, Z. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Purpose: The aim of this study is to determine the relationship between the peak power obtained during force-velocity test with arms and/or legs and thrower performance. Material and Method: Seven national and international throwers (age: 20 ± 2; height: 181 ± 7 cm; Weight: 86 ± 14 kg) have undertaken a force-velocity test on a cycle ergometer (Monark type 894 E) with arms and legs. Thrower performance was measured. Arm and leg muscle mass was evaluated by Jones and Pearson method (1969). Results: Leg peak power obtained during force-velocity test was 1082 ± 286 W. When expressed to weight or muscle mass, leg peak power values were 13 ±3 W/kg and 95±26 liter of muscle respectively. Arm peak power measured during force-velocity test was 597 ± 138 W. When expressed to body mass or muscle mass, arm peak power values were 7 ±2 W/kg and 217±45 liter of muscle respectively. The arm/leg ratio was 0,6 ±0,1 (0,4 - 0,8). There is a significant relationship between the thrower performance and the peak relative power measured for arms (r=0.89; p <0.05) and for legs (r = 0.57; p <0.05). Discussion: The significant relationships between performance and the arm or leg-peak power obtained during force-velocity test are a result in agreement with literature data (xxx, 19XX). The force-velocity test seems to be a good proof to evaluate arms and/or legs peak muscle power in throwers.